Rapid Sonochemical Approach Produces Functionalized Fe3o4 Nanoparticles with Excellent Magnetic, Colloidal, and Relaxivity Properties for Mri Application - Melo-Freire, R (American Chemical Society, 2017)
Functionalized Fe3O4 nanoparticles (NPs) have emerged as a promising contrast agent for magnetic resonance imaging (MRI). Their synthesis and functionalization methodology strongly affect their performance in vivo. The methodology most used in the literature for the synthesis of Fe3O4 NPs is thermal decomposition, which has proven to be time-consuming, expensive, and laborious, as it requires further ligand exchange strategies to transfer the as-synthesized nanoparticles from organic to aqueous solvents. This work describes a rapid and facile sonochemical methodology to synthesize and functionalize Fe3O4 NPs with excellent physicochemical properties for MRI. This sonochemistry approach was used to produce, in 12 min, Fe3O4 NPs functionalized with polysodium acrylate (PAANa), trisodium citrate (CIT), branched polyethylenimine (BPEI), and sodium oleate. X-ray diffraction and transmission electron microscopy demonstrated that the NPs were composed of a single inverse spinel phase with an average diameter of 9-11 nm and a narrow size distribution. Mössbauer spectroscopy and magnetic measurements confirmed that the obtained NPs were transitioning to the superparamagnetic regime and possessed excellent magnetization saturation values (59-77 emu/g). Fourier transform infrared spectroscopy proved that the sonochemistry approach provided conditions that induced a strong interaction between Fe3O4 and the coating agents. Furthermore, dynamic light-scattering experiments evidenced that samples coated with PAANa, CIT, and BPEI possess colloidal stability in aqueous solvents. Emphasis must be placed on PAANa-coated NPs, which also presented remarkable colloidal stability under simulated physiological conditions. Finally, the obtained NPs exhibited great potential to be applied as an MRI contrast agent. The transverse relaxivity values of the NPs synthesized in this work (277-439 mM-1 s-1) were greater than those of commercial NPs and those prepared using other methodologies. Therefore, this work represents significant progress in the preparation of Fe3O4 NPs, providing a method to prepare high-quality materials in a rapid, cost-effective, and facile manner. © 2017 American Chemical Society.